The FMR1 gene, infertility, and reproductive decision-making: a review - Pastore, Lisa M.; Johnson, Joshua (Frontiers in Genetics, 2014)
The strongest association between FMR1 and the ovary in humans is the increased risk of premature ovarian failure in women who carry the premutation level of CGG repeats (55-199 CGGs). Research on the FMR1 gene has extended to other endpoints of relevance in the OB/GYN setting for women, including infertility and ovarian hormones. After reviewing the nomenclature changes that have occurred in recent years, this article reviews the evidence linking the length of the FMR1 repeat length to fertility and ovarian hormones (follicle stimulating hormone and anti-mullerian hormone as the primary methods to assess ovarian reserve in clinical settings). The literature is inconsistent on the association between the FMR1 trinucleotide repeat length and infertility. Elevated levels of follicle stimulating hormone have been found in women who carry the premutation; however the literature on the relationship between anti-mullerian hormone and the CGG repeat length are too disparate in design to make a summary statement. This article considers the implications of two transgenic mouse models (FXPM 130R and YAC90R) for theories on pathogenesis related to ovarian endpoints. Given the current screening/testing recommendations for reproductive age females and the variability of screening protocols in clinics, future research is recommended on pretest and posttest genetic counseling needs. Future research is also needed on ovarian health measurements across a range of CGG repeat lengths in order to interpret FMR1 test results in reproductive age women; the inconsistencies in the literature make it quite challenging to advise women on their risks related to FMR1 repeat length.